Digital entrepreneurship in the context of the Republic of Serbia - Đoković, Goran; Čelik, Petar; Arsić, Milica (Industrija, 2025)
Abstract: The concept of digital entrepreneurship is a topical issue that significantly affects the contemporary business practice and management theory. Therefore, the main goal of the research was to point out the importance of digital entrepreneurship for the business of modern organisations, as well as to analyse the potential for digital entrepreneurship on the example of companies from the Republic of Serbia in the context of employees’ gender and work experiences.  From a scientific point of view, the paper provides an insight into the theoretical framework of digital entrepreneurship, which includes current definitions and scientific approaches published in world relevant scientific bases. The empirical significance of the research is based on the results of a survey that included 124 employees (N=124), from different companies which have implemented digital innovations or used digital technologies for business model transformation in the Republic of Serbia. Keywords: digital entrepreneurship, entrepreneurship, digital innovation, digital business, digital transformation
Keywords: digital entrepreneurship, entrepreneurship, digital innovation, digital business, digital transformation